Toward Indonesian Islamic News Media Framing Roles On International Dehumanization Issues - Averoes Fikria; Uswatul Wadhichatis Saniyyah (EL- Hayah, 2025)
ABSTRACT The purpose of this research is to examine how Indonesian Islamic media frames international dehumanization issues. The researcher involves qualitative descriptive methods in order to summarize the data analysis through Goffman's media framing theory approach by studying the typology of prophetic and provocative narratives. The data is collected from any Indonesian Islamic media platform. Based on the credibility of the media, researchers have found 50 sites that fulfill the eligibility as Islamic media. The results imply that of the research, 18 sites have prophetic narratives. It is clear from these 18 sites that the narratives employed in prophetic pieces typically present the news in a way that does not elicit strong feelings from readers while offering adaptable and non- threatening pictures and descriptions, 19 sites have provocative headlines. It had extremely strong opinions about the issue, suggesting it to be either compulsory or haram. Aside from that, this section of news media is neither provocative nor prophetic because its articles combine elements of both. Under the right conditions, future researchers should be able to explore other significant effects of media framing through journalistic typology. Keywords: Islamic, News Media, Media Framing, Dehumanization.